Running speed during training and percent body fat predict race time in recreational male marathoners - Barandun U; Knechtle B; Knechtle P; Klipstein A; Rust CA; Rosemann T; Lepers R (Dove Medical Press, 2012)
Background: Recent studies have shown that personal best marathon time is a strong predictor of race time in male ultramarathoners. We aimed to determine variables predictive of marathon race time in recreational male marathoners by using the same characteristics of anthropometry and training as used for ultramarathoners.Methods: Anthropometric and training characteristics of 126 recreational male marathoners were bivariately and multivariately related to marathon race times.Results: After multivariate regression, running speed of the training units (β=-0.52, P<0.0001) and percent body fat (β=0.27, P <0.0001) were the two variables most strongly correlated with marathon race times. Marathon race time for recreational male runners may be estimated to some extent by using the following equation (r2 = 0.44): race time (minutes) = 326.3 + 2.394 × (percent body fat, %) – 12.06 × (speed in training, km/hours). Running speed during training sessions correlated with prerace percent body fat (r=0.33, P=0.0002). The model including anthropometric and training variables explained 44% of the variance of marathon race times, whereas running speed during training sessions alone explained 40%. Thus, training speed was more predictive of marathon performance times than anthropometric characteristics.Conclusion: The present results suggest that low body fat and running speed during training close to race pace (about 11 km/hour) are two key factors for a fast marathon race time in recreational male marathoner runners.Keywords: body fat, skinfold thickness, anthropometry, endurance, athlete